KARAKTERISASI METABOLIT SEKUNDER DARI DAUN MANGROVE Rhizopora stylosa SEBAGAI ANTIOKSIDAN (CHARACTERIZATION OF SECONDARY METABOLITE MANGROVE LEAVES Rhizopora stylosa SPECIES AS ANTIOXIDANTS) - Septian Triadi Syahputra; Ajuk Sapar; Ari Widiyantoro (Indonesian Journal of Pure and Applied Chemistry, 2022)
Mangrove leaves or also known as “bakau” by the people of Mempawah Regency, which has (Rhizopora stylose) species containing alkaloids, flavonoids, steroids, terpenoids, phenolics, and saponins that can be used as antioxidant compounds. This study was aimed to determine the antioxidant activity of extracts and secondary metabolite fractions, and also to determine the characteristics of isolate compounds from mangrove leaves (Rhizopora stylose). Maceration of 1.57 kg of dry powder of mangrove leaves (Rhizopora stylose) with methanol as a solvent obtained a crude extract of 141.13 g of methanol with a percent yield of 8.98%. Partitioning the crude methanol extract obtained the n-hexane, dichloromethane, ethylacetate, and residue fractions by weight and percent yield, respectively, namely 6.95 g (0.44%), 26.74 g (1.70%), 26 .66 (1.69%), and 25.75 g (1.64%). The results of the antioxidant activity test showed that the dichloromethane fraction had a better antioxidant activity with an IC50 value of 121.314 g/mL. Separation and purification of the dichloromethane fraction to obtain isolates were carried out by column chromatography in order to obtain pure isolates which were characterized by the appearance of a single spot on the tested plate with various eluents, namely, isolate F7. The 1H-NMR data for isolate F7 showed chemical shifts for aromatic protons of 8.52 ppm, 7.70 ppm, 7.67 ppm, protons for tertiary C of 5.41 ppm, and protons for methyl and methylene of 3.50 ppm, 3.47 ppm, 1.59 ppm, 1.23 ppm, 1.05 ppm, and 0.84 ppm. H-NMR data showed that isolate F7 had similarities with the chemical shift of p-Oxy-2-Ethylhexyl benzaldehyde, namely 7.71 ppm, 7.54 ppm, 4.22 ppm, 1.68 ppm, 1.35 ppm, 1.32 ppm, 1.30 ppm, 0.90 ppm but different in the alkoxy substituent position from isolate F7 which was in the meta position